Lignocellulosic xylitol production from corncob using engineered Kluyveromycesmarxianus - Zhang, Jia; Xu, Teng; Wang, Xiaohang; Jing, Xiaoyan; Zhang, Jia; Hong, Jiong; Xu, Jian; Wang, Jichao (Frontiers in Bioengineering and Biotechnology, 2022)
Xylitol production from lignocellulose hydrolysate is a sustainable and environment-friendly process. In this study, a systematic process from corncob waste to xylitol is described. Firstly, the corncobs are hydrolyzed by acid to a hydrolysate. Secondly, Kluyveromyces marxianus YZJQ016 derived from K. marxianus YZJ074, constructed by overexpressing ScGAL2-N376F from Saccharomyces cerevisiae, CtXYL1 from Candida tropicali, and KmZWF1 from K. marxianus, produces xylitol from the hydrolysate. Ten xylose reductase genes were evaluated, and CtXYL1 proved best owning to the highest catalytic activity under the control of KmGAPDH promoter. A 5 L fermenter at 42℃ produced 105.22 g/L xylitol using K. marxianus YZJQ016 - the highest production reported to date from corncob hydrolysate. Finally, for crystallization of the xylitol, the best conditions were 50% (v/v) methanol as antisolvent, at 25℃, with purity and yield of 99~100% and 74%, respectively - the highest yield reported to date.